Upaya Pemberdayaan Tanah Wakaf Produktif bagi Kesejahteraan Ummat - Al-Hadi, Abu Azam (ISLAMICA: Jurnal Studi Keislaman, 2009)
This paper is aimed at discussing the notion of endowment as a means to increase the economic prosperity of the Muslim society in Indonesia. It argues that the Muslims of Indonesia have enough endowed properties but lack a proper management in running them. This leads to the misuse of the properties on the one hand, and to the failure to achieve the proposed aims for which these properties are endowed. This paper suggests ways to run the properties properly and the reasonable objectives for which the endowment may be aimed at.